Gestation Period and Calving Interval of Balinese Cows at Various Parities in CV. Darmapuri Agro Semesta Klungkung Bali - Rizki, Fifi Firnanda; Kusumawati, Enike Dwi; Warmadewi, Dewi Ayu (Universitas Bengkulu, 2025)
The purpose of this study is to identify the effect of parity on calving interval and gestation period in Balinese cattle in CV. Darmapuri Agro Semesta Klungkung Bali. The research method used in this study is a survey method conducted on female Balinese cows that have undergone Artificial Insemination (AI) at least once, are pregnant, or have given birth, as well as the results of interviews and direct observations. The research material used in this study consists of Balinese cattle, specifically 10 female Balinese cows, which are selected annually over five years, resulting in a total of 50 heads. There are five treatments, namely 1st parity (P1), 2nd parity (P2), 3rd parity (P3), 4th parity (P4), and 5th parity (P5). The variables observed were gestation period and calving interval. Data were analysed using analysis of variance with a completely randomised design, followed by the Least Significant Difference test. The results of the study showed that parity had a highly significant effect (P < 0.01) on gestation period and calving interval. The duration of gestation from shortest to longest in sequence is P5 (272.00 ± 23.07 days), P2 (276.90 ± 24.16 days), P1 (307.00 ± 20.65 days), P3 (322.40 ±35.14 days), P4 (325.70±27.62). Meanwhile, the calving interval values are P1 (0.00 ± 0.00 days), P2 (351.90 ± 85.61 days), P4 (376.90 ± 103.69 days), P5 (383.30 ± 94.58 days), and P3 (603.20 ± 218.30 days). The second (P2) and fifth (P5) gestation periods were significantly shorter than those of the first parity (P1). The shortest gestation period is at the 5th parity, while the shortest calving interval is at the 2nd parity. This study concludes that the various parities on calving interval and gestation period show a significant difference.